THE PROCEDURE FOR GATHERING EVIDENCE IN CONDUCTING A PERIOD COST AUDIT - M.Nizekeev; O.Nizomov (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2023)
This article describes the process of gathering evidence in a period cost audit. As a result of the research, recommendations were developed to improve the evidence collection process.